Answer:
G) the expression has the greatest value when 6.
ie,
![xy=b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jbphzg4g94c6xkklzkwmqfhwcuddmf8o82.png)
Explanation:
F) Given expression is -xy and to find the greatest value of that expression when
and
Substitute the given values of
and
is the given expression
![-xy=-(2)(-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uqlsak5dgndegg2hzzwa1qh0irfiw981d5.png)
![=-(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1h1mrs4todquqd1mghe4l0stcobhpnsv53.png)
![-xy=-6\hfill(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s2pg63lgzh6ls696dcjz483l0zo1hgv82q.png)
h) x-y
Given expression is x-y
substitute x=-2, y=-3 is above expression we get
![x-y=-2-(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4pw6q93290ujsoorg0jyh9tgqkltygesif.png)
![-2+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ruunqusld9cbkupmg3n4zgcvxdlb5lq8iw.png)
![x-y=1\hfill(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q6s4e3b9n0pc46dkmyq8qn27k5uux9z60g.png)
G, xy
Given expression is xy
Substitute x=-2, y=-3 in above expression
![xy=(-2)(-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/voj7az2i8cnm3jl12s3t4p94pgmb0eeqr0.png)
![xy=6\hfill(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fnlje2p5uhf2sxq28c4xlf9lmznh6jyb7b.png)
I) -x-y
Given expression is -x-y
put x=-2, y=-3 in above expression
![-x-y=-(-2)-(-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ae0o80csm8knqhxelg54hp3cn9ns31o55l.png)
![=2+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o78l07z30krhu0z0z3vkg7xj4umdq8ipa4.png)
![-x-y=5\hfill(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m9y23tfgl6bdayt4d4kuf0re34vsksbyxi.png)
Now comparing the greatest values equation (1), (2), (3) and (4) we get
Equation (3) xy=6 has the greatest value